2018
DOI: 10.1371/journal.pone.0205908
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ocean acidification on the byssal threads of the blue mussel (Mytilus edulis)

Abstract: Blue mussel (Mytilus edulis) produce byssal threads to anchor themselves to the substrate. These threads are always exposed to the surrounding environmental conditions. Understanding how environmental pH affects these threads is crucial in understanding how climate change can affect mussels. This work examines three factors (load at failure, thread extensibility, and total thread counts) that indicate the performance of byssal threads as well as condition index to assess impacts on the physiological condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Mussel attachment strength is the product of byssal thread number and quality, both of which have been shown to vary with environmental conditions. For example, elevated pCO 2 (>1200 μatm) lowers thread strength in Mytilus trossulus (O'Donnell et al ., 2013; George and Carrington, 2018), thread strength and production in Mytilus coruscus and Pinctada fucata (Zhao et al ., 2017; Li et al ., 2017; Kong et al ., 2019), and thread strength in Mytilus edulis (Kong et al ., 2019, but see Dickey et al ., 2018). However, there is little consensus when whole animal attachment is measured, with negative, neutral, and positive effects of elevated pCO 2 observed in Mytilus galloprovincialis , M. edulis, Xenostrobus securis , and M. coruscus , respectively (Babarro et al ., 2018; Clements et al ., 2018; Sui et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mussel attachment strength is the product of byssal thread number and quality, both of which have been shown to vary with environmental conditions. For example, elevated pCO 2 (>1200 μatm) lowers thread strength in Mytilus trossulus (O'Donnell et al ., 2013; George and Carrington, 2018), thread strength and production in Mytilus coruscus and Pinctada fucata (Zhao et al ., 2017; Li et al ., 2017; Kong et al ., 2019), and thread strength in Mytilus edulis (Kong et al ., 2019, but see Dickey et al ., 2018). However, there is little consensus when whole animal attachment is measured, with negative, neutral, and positive effects of elevated pCO 2 observed in Mytilus galloprovincialis , M. edulis, Xenostrobus securis , and M. coruscus , respectively (Babarro et al ., 2018; Clements et al ., 2018; Sui et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Calcification rates of the larval, juvenile and adult stages of C. virginica will be hindered under the acidic conditions expected to occur within the next century (Miller et al 2009;Ries et al 2009;Waldbusser et al 2011). Larval growth, calcification rates and overall health of M. edulis will be inhibited during this same time period (Gazeau et al 2007;Beesley et al 2008;Gazeau et al 2010), but several studies (Beesley et al 2008;Thomsen & Melzner, 2010;Dickey et al 2018) suggest that M. edulis metabolism, tissue condition and thread production will not be affected. In contrast, studies with Mytilus trossulus (Gould 1850) on the U.S. Washington coast found that byssal thread number and attachment strength were negatively affected by higher temperature (25°C versus 10°C) and secreted adhesives did not cure well at pH < 8 (O'Donnell et al 2013; George & Carrington 2018;Newcomb et al 2019).…”
Section: Acidification Impactsmentioning
confidence: 99%
“…2008; Thomsen & Melzner, 2010; Dickey et al . 2018) suggest that M. edulis metabolism, tissue condition and thread production will not be affected. In contrast, studies with Mytilus trossulus (Gould 1850) on the U.S. Washington coast found that byssal thread number and attachment strength were negatively affected by higher temperature (25°C versus 10°C) and secreted adhesives did not cure well at pH < 8 (O’Donnell et al .…”
Section: Resilience Of the Aquaculture Industrymentioning
confidence: 99%